2018
DOI: 10.1016/j.celrep.2018.03.131
|View full text |Cite
|
Sign up to set email alerts
|

CSF1R+ Macrophages Sustain Pancreatic Tumor Growth through T Cell Suppression and Maintenance of Key Gene Programs that Define the Squamous Subtype

Abstract: SummaryPancreatic ductal adenocarcinoma (PDAC) is resistant to most therapies including single-agent immunotherapy and has a dense desmoplastic stroma, and most patients present with advanced metastatic disease. We reveal that macrophages are the dominant leukocyte population both in human PDAC stroma and autochthonous models, with an important functional contribution to the squamous subtype of human PDAC. We targeted macrophages in a genetic PDAC model using AZD7507, a potent selective inhibitor of CSF1R. AZD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
163
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(186 citation statements)
references
References 44 publications
10
163
0
Order By: Relevance
“…Using available PDA transcriptome data from the ICGC and the TCGA consortia, we found that levels of gene expression signatures indicative of MAP kinase activity (Biocarta_ERK_Pathway and MAPK Signature (21)) were higher in PDA subtypes (squamous/basal-like/quasimesenchymal) characterized by abundance of macrophage-related transcripts and immunosuppressive signaling (7,13,14) ( Figure 1A and Supplementary Figure 1A-B ). The enrichment of MAPK activity signatures in aggressive molecular subtype of PDA was also confirmed in additional 14 datasets of PDA ( Supplementary Figure 1C-D ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using available PDA transcriptome data from the ICGC and the TCGA consortia, we found that levels of gene expression signatures indicative of MAP kinase activity (Biocarta_ERK_Pathway and MAPK Signature (21)) were higher in PDA subtypes (squamous/basal-like/quasimesenchymal) characterized by abundance of macrophage-related transcripts and immunosuppressive signaling (7,13,14) ( Figure 1A and Supplementary Figure 1A-B ). The enrichment of MAPK activity signatures in aggressive molecular subtype of PDA was also confirmed in additional 14 datasets of PDA ( Supplementary Figure 1C-D ).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological and genetic depletion of myeloid cells (i.e., macrophages or neutrophils) in autochthonous model of PDA has been shown to dramatically alter gene programs that specify molecular subtypes (13,14). Investigation of immune-related cell signatures in bulk RNA sequencing has proven useful to estimate the composition of immune cell populations as well as transcriptional programs underpinning mechanisms of immune regulation (7,22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations